2018
DOI: 10.1080/00380768.2017.1421436
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of co-inoculation ofBradyrhizobium japonicumSAY3-7 andStreptomyces griseoflavusP4 on plant growth, nodulation, nitrogen fixation, nutrient uptake, and yield of soybean in a field condition

Abstract: Co-inoculation of nitrogen-fixing bacteria with plant growth-promoting bacteria has become more popular than single inoculation of rhizobia or plant-growth-promoting bacteria because of the synergy of these bacteria in increasing soybean yield and nitrogen fixation. This study was conducted to investigate the effects of Bradyrhizobium japonicum SAY3-7 and Streptomyces griseoflavus P4 co-inoculation on plant growth, nodulation, nitrogen fixation, nutrient uptake, and seed yield of the 'Yezin-6' soybean cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 35 publications
5
11
0
Order By: Relevance
“…The application of the biofertilizer produced from Bradyrhizobium and S. griseoflavus P4 increased the N, P, and K uptakes of soybean and mung bean compared with the control (Tables 7-9). These results support our previous finding that inoculation of Bradyrhizobium with P4 significantly increased the N, P, and K uptakes of soybean compared with an un-inoculated control [48,49]. Beneficial microorganisms can keep the soil environment rich in all kinds of micro-and macronutrients via nitrogen fixation, phosphate and potassium solubilization or mineralization, the release of plant growth regulators, the production of antibiotics, and the biodegradation of organic matter in the soil [18].…”
Section: Discussionsupporting
confidence: 88%
“…The application of the biofertilizer produced from Bradyrhizobium and S. griseoflavus P4 increased the N, P, and K uptakes of soybean and mung bean compared with the control (Tables 7-9). These results support our previous finding that inoculation of Bradyrhizobium with P4 significantly increased the N, P, and K uptakes of soybean compared with an un-inoculated control [48,49]. Beneficial microorganisms can keep the soil environment rich in all kinds of micro-and macronutrients via nitrogen fixation, phosphate and potassium solubilization or mineralization, the release of plant growth regulators, the production of antibiotics, and the biodegradation of organic matter in the soil [18].…”
Section: Discussionsupporting
confidence: 88%
“…Kozieł et al (2013) and Martyniuk et al (2018) report that a significant increase in the number of pods on the soybean plant is obtained under the influence of inoculation of seeds with symbiotic bacteria. In contrast, Htwe et al (2018) did not show the effect of bacterial inoculants on the number of pods per plant.…”
Section: Resultsmentioning
confidence: 59%
“…Pantoea dispersa MPJ9 and Pseudomonas putida MPJ6 isolates have been tested for their ability to produce siderophores, showing a great Fe chelating potential under Fe deficient conditions; in this study, the Fe content of mung beans was increased 3.4-fold, protein content 2-fold, and carbohydrate content 1.5-fold after inoculation with the strain of P. dispersa [88]. Co-inoculation with Bradyrhizobium japonicum SAY3-7 and Streptomyces griseoflavus P4 improved N, P, K, Ca, and magnesium (Mg) uptake in soybean plants [89]. A recent study showed that seed coating with Zn solution in combination with a Zn solubilizer PGPB, Enterobacter sp.…”
mentioning
confidence: 62%
“…Chickpea, Soybean, Wheat Increase Zn uptake [86,90] Acinetobacter tandoii SRI-305, Enterobacter ludwigii SRI-229 Chickpea, Pigeonpea Increase Fe, Zn, Cu, Mn, and Ca uptake [87] Bradyrhizobium japonicum SAY3-7 and Streptomyces griseoflavus P4 Soybean Increase N, P, K, Ca, and Mg uptake [89] Pantoea dispersa MPJ9, Pseudomonas putida MPJ6 Mung bean Increase Fe uptake [88] Bacillus aryabhattai S10 + B. subtilis ZM63 Mung bean Increase N, P, and K uptake [91] Symbion-K (Frauteria aurantia), Pseudomonas sp. RA6, P. citronellis (PC), Serratia sp.…”
Section: Lentil Peamentioning
confidence: 99%